Twenty years after Doha: An analysis of the use of the TRIPS Agreement's public health flexibilities in India - Muhammad Zaheer Abbas (South Centre, 2022)
The World Trade Organization (WTO) linked intellectual property protection with trade. The WTO Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement), however, included a number of public health flexibilities in order to provide latitude to the Member States to tailor their national patent laws to fit their individual needs. In 2001, the Doha Declaration further clarified and reaffirmed the existing TRIPS flexibilities. This paper argues that India has taken the lead role in enacting the TRIPS Agreement's substantive and procedural patent flexibilities by introducing unique legislative measures to deal with the problem of access to medicines. This article evaluates India's use of section 3(d) as a subject matter exclusivity provision. It examines constitutional validity and TRIPS compliance of section 3(d). It also evaluates India's use of the flexibility to define the term "inventive step". Moreover, this article evaluates India's use of compulsory licensing, the most notable exception to patent rights provided under the TRIPS Agreement. This empirical study is important in the context of the COVID-19 pandemic, which has once again highlighted the same public health issues that the Doha Declaration sought to address twenty years ago.
Keywords: 300; Access to Medicines; Compulsory Licenses; COVID-19; Doha Declaration on the TRIPS Agreement and Public Health; Flexibilities; Health; India; Intellectual Property; Inventive Step; Pandemic; Patent; Patent Law; Public Health; Subject Matter Exclusions; TRIPS; TRIPS Agreement; TRIPS Flexibilities; World Trade Organization (WTO)